Design of a tidal power park and a wave power park with a techno-economical approach - Bitowt, Mikael; Johansson, Malin (My University, 2013)
This report focuses on the infrastructure of a cost efficient subsea collection grid for a tidal power park and a wave power park, 50 MW and 2.5 MW, respectively. A study has been made on subsea components, some operating today and other under development, for an offshore collection grid. Also the possibility to connect the tidal park to an offshore wind farm has been investigated. The cable dimensioning of the collection grid is based on the cost of cables and lost revenue from the power loss. AC and DC collection grids at the voltages between 0.69-14 kV and with radial and star infrastructure, respectively, have been investigated. A DC system will always be cheaper than an AC system (as long as the generator can excite high enough voltage for the collection grid) since a converter is required independent of the voltage type. However, there are no manufacturers today that offer DC cables for the considered voltage range. One of the most expensive and weakest points of a system are the connectors. Therefore the star connection is preferable over the radial pattern, due to the lower number of connectors. The preferred collection grid, for both the tidal and the wave case, is a DC grid in star connection. The cost of the cables for these systems are approximated to be 7 424 kkr at 9.3 kV and 249 kkr at 1.4 kV, respectively. However, if it is not possible to order DC cables at this low voltage or they become too expensive, an AC system should be used instead. The preferred AC system is then a star connection at 6.6 kV and 3.3 kV, tidal and wave, respectively. The cable losses for the selected systems reaches a maximum of 0.4% when considering a whole system. All the components required for these applications will need to be special designed for its purpose and will therefore be expensive. For the transmission from the park to the grid, three options have been studied: transmission at collection grid voltage, transmission with higher voltage using a transformer and sharing transmission cables with a large wind power park (in this study Gwynt y M^or). The most cost effective option for distances between 1.8 km to 19.3 km is to use an own cable at 66 kVAC with a cross-sectional area of 500 mm2. At distances longer than 19.3 km the most cost effective solution is to share the transmission cables at 132 kVAC and 500 mm2 with Gwynt y M^or, when accounting for 3 % rental cost of using Gwynt y M^or's components. If it would be possible to increase the cross-sectional area of the Gwynt y M^or's transmission cables from 500 mm2 to 630 mm2, this transmission would become the most cost effective solution at distances longer than 4.6 km (when using a rental share of 3 %). The reason for this result is that the cost of losses are lower and there is no cost in lost revenue for the 630 mm2 cables, due to that they are over dimensioned.
Keywords: Elkraftteknik; Electric power engineering